The Magazine of Art. (Londen : Petter and Gallpin, 1878)
The Magazine of Art was an illustrated monthly British journal devoted to the visual arts, published from May 1878 to July 1904 in London and New York City by Cassell, Petter, Galpin & Co. It included reviews of exhibitions, articles about artists and all branches of the visual arts, as well as some poetry, and was lavishly illustrated by leading wood-engravers of the period such as William Biscombe Gardner (wikipedia)
Https://en.wikipedia.org/wiki/The_Magazine_of_Art
Online: https://archive.org/details/magazineofart05londuoft
Catalog.hathitrust.org/Record/000049695: 1878 latere jrg (login)
Engels
Tijdschriften